Rural banking, an infrastructural input for hill area development - Sikidar, Sujit (New Delhi : Anmol Publications, 1992)
Study with reference to selected districts in Assam; covers chiefly the period, 1988-1991.
Includes bibliographical references (p. [163]-166).
Keywords: Agricultural credit -- India -- Assam; Rural development -- India -- Assam